Mapping the Sustainable Development Goals Relationships - Fonseca, Luís (2020)
Sustainable development addresses humanity’s aspiration for a better life while observing the limitations imposed by nature. In 2015, the United Nations General Assembly approved the 17 Sustainable Development Goals (SDGs) with the aim to foster the organizational operationalization and integration of sustainability and, therefore, to address the current and forthcoming stakeholder needs and ensure a better and sustainable future for all, balancing the economic, social, and environmental development. However, it is not entirely clear which are the mutual relationships among the 17 SDGs and this study aims to tackle this research gap. The results of the correlation confirm that Poverty elimination (SDG1) and Good health and well-being (SDG3) have synergetic relationships with most of the other goals. SDG7 (Affordable and clean energy) has significant relationships with other SDGs (e.g., SDG1 (No poverty), SDG2 (Zero hunger), SDG3 (Good health and well-being), SDG8 (Decent work and economic growth), SDG13 (Climate action)). However, there is a moderate negative correlation with SDG12 (Responsible consumption and production), which emphasizes the need to improve energy efficiency, increase the share of clean and renewable energies and improve sustainable consumption patterns worldwide. There is also confirmation that SDG12 (Responsible consumption and production) is the goal strongly associated with trade-offs. To sum up, this research suggests that change towards achieving the Sustainable Development Goals offers many opportunities for reinforcing rather than inhibiting itself. However, some SDGs show no significant correlation with other SDGs (e.g., SDG13 (Climate action) and SDG17 (Partnerships for the goals), which highlights the need for future research.